Formulasi Sabun Batang Transparan Dari Ekstrak Sirih Cina (Peperomia pellucida L. Kunth) - Widiastuti, Rina; Lestari, Dilla Feby; Ismiyati (Politeknik Kesehatan Bhakti Setya Indonesia, 2024)
Transparent bar soap is a soap innovation with a clear appearance, produces soft foam, has an attractive sparkle, and has the ability to retain active ingredients. This study developed transparent bar soap using ethanol extract of Chinese betel (Peperomia pellucida L. Kunth) which has antibacterial activity (inhibition zone 13.73 mm) and strong antioxidant (IC50 = 32.94 microgram/mL). This study aims to formulate transparent soap of ethanol extract of Chinese betel with variations of sucrose and 96% ethanol. This study was conducted with pre-experimental method using post-test only design in the laboratory. Chinese betel samples were collected from Magelang Regency using purposive sampling method and extracted using maceration method with 70% ethanol solvent. The extract was then formulated into transparent soap bars with varying levels of sucrose and 96% ethanol: Formulation 1 (7.5%: 15%), Formulation 2 (9.5%: 13%), and Formulation 3 (11.5%: 11%). Tests included organoleptic test, pH, foam height, cleanness, and transparency. The results showed that the transparent soap bar preparation in formulation 1 had a solid shape with elastic hard texture, dark brown colour. Formulation 2 also has a solid shape, elastic hard texture, and lighter brown colour. Formulation 3 produces the same shape and texture, with a light brown colour and has the most transparent level of transparency. All formulas have a soap pH value of 10, in accordance with SNI standards which range from 9-11. Foam height in all formulations met the set standard of 1.3-22 cm. In the cleanability test, formulation 2 has the highest level of cleanliness, followed by formulation 3 and formulation 1.